Development and Psychometric Properties of the Social Relationship Scale - Mehmet Fatih Köse; Mehmet Ata Öztürk; Ayşegül Acar (İstanbul Üniversitesi Sosyoloji Dergisi)
This study seeks to develop a valid, reliable metric for holistically measuring the scope and depth of interpersonal social relations. Several studies are found in the literature to have focused on interpersonal and social relations and the components making up these relations. Because numerous scales are encountered focusing mainly on the private sphere such as relationships between friends and family members and on closed environments such as relationship that occur in school, an excellent contribution to the literature would be a study that seeks to develop a scale able to holistically evaluate the scope and depth of social relations that takes into account all personal and social spheres. The research group consists of 973 university students and 1,158 young adults aged 25–29. We conducted both exploratory factor analyses (EFA) and confirmatory factor analyses (CFA) to determine the scale’s structural properties. The EFA results reveal social relations to be evaluable under three subdimensions (i.e., family, kinship/neighborhood relations, and friendship). The CFA confirmed the scale to be composed of three factors and to have acceptable fit for use with both university students (x 2 /df = 5.02; RMSEA = .06; GFI = .97; CFI = .95; NFI = .94) and young adults aged 25–29 (x 2 /df = 5.09; RMSEA = .06; GFI = .98; CFI = .97; NFI = .96). Internal consistency values were found to be .79 for the entire scale and .73, .74, and .67 for the respective subdimensions. The study’s results provide robust evidence that the Social Relations Scale is a valid and reliable scale for measuring the scope and depth of the social relations university students and young adults build.